Characteristics of corruption crimes in the perspective of criminology - Supardi Hamid (Trigin Publisher, 2023)
This study aims to men analysis the causes of corruptors have yet to be charged by the applicable legal provisions, as well as to examine the current law enforcement problems of corruption. The type of research in this study is the normative juridical method, whose other name is doctrinal legal research, also known as library research or document study because this research is carried out or aimed only at written regulations or other legal materials. The approaches used by researchers in compiling this research are, among others: the Statute Approach and the case approach. Every ruler tends to maintain his power, and it is also possible that with his power, he can prepare himself to prevent or avoid legal proceedings that can potentially execute him for his arbitrariness.